Carbon nitride nanosheets as visible light photocatalytic initiators and crosslinkers for hydrogels with thermoresponsive turbidity - Liu, Jian; An, T.; Chen, Z.; Wang, Z.; Zhou, H.; Fan, T.; Zhang, D.; Antonietti, M. (R S C Publications, 2017)
© The Royal Society of Chemistry 2017. Graphitic carbon nitride (g-C3N4) has emerged as an active visible-light-driven photo(electro)catalyst. However, the rediscovery of g-C3N4has also spurred enormous interest in other, very versatile applications beyond catalysis. Herein, graphitic carbon nitride nanosheets could be used as photocatalytic initiators and cross-linking sites for the temperature responsive poly(N-isopropylacrylamide) hydrogel without any sacrificial agents or co-initiators. A prototype of a temperature controlled smart window based on the hydrogel composite was made by coating the hydrogel composite onto glass. It is believed that the combination of g-C3N4chemistry and conventional hydrogel or polymer chemistry can lead to further promising applications.